Box Station Parametric Study with Time History Dynamic Analysis - Sengara, I Wayan; Basarah, Yuamar I.; Sulaiman, Ahmad; Sibagariang, Sarah M.T. (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The performance of an underground station structure subjected to an earthquake can be evaluated by looking at deformation as well as forces and bending moments that occur in the structure. Most design practices adopt simplified approaches, such as the free field deformation method and pseudo-static approaches, which have a high level of uncertainty. Therefore, it is necessary to perform dynamic time-history analysis to verify the results of the simplified approach. Dynamic modeling is considered a more appropriate approach because it better represents seismic shaking in evaluating the seismic response of underground structures. This study performed time-history dynamic analysis by conducting a parametric study. The study was conducted to determine the effect of parameters such as site class, peak base acceleration (PBA) ground-motion intensity, and the type of seismic mechanism on the deformation response. Based on the parametric study, it was found that the stiffer the site class, the smaller the relative deformation of the resulting underground structure. The greater the PBA intensity value, the greater the relative deformation. Relative deformation in the wall structure subjected to a subduction earthquake is more significant compared to that of a shallow crustal earthquake.